The Study of Citrus Peels (Citrus amblycarpa) Mass Ratio Substitution on Physicochemical of Rich-Antioxidant of Liang Tea - Yohana S. K. Dewi (Poltekkes Kemenkes Palu, 2022)
The purpose of this study was to obtain the mass ratio substitution of citrus peel in the rich-antioxidant of liang tea formulation which produced the best physicochemical characteristics. The ingredients for making rich-antioxidant of liang tea are dried herbal plant ingredients consisting of muje leaves (D. chinensis), nanas kerang leaves (Tradescantia spathacea Sw.), origanum leaves (Origanum vulgare Wilder), pandan leaves (Pandanus amaryllifolius), stem bark from Secang wood (Caesalpinia sappan), midrib skin from Lidah Buaya (Aloe vera chinensis) and jeruk sambal peels (Citrus amblycarpa) with mass ratios according to treatment. The treatment was in the form of mass ratio of liang tea and citrus amblycarpa peel (100:0; 90:10; 80:20; 70:30; 60:40; 50:50 and 40:60). Parameters to observed are physical characters include color, pH and chemical characters include qualitative phytochemical testing, vitamin C content, total phenol content, total flavonoid content and antioxidant activity with DPPH inhibitory activity. The results showed that the formulation of the mass ratio of liang tea: citrus peel 70:30 had the highest total phenol content, total flavonoid and antioxidant activity (63,82 ± 3,70 mg GAE/g ext, 47,73 ± 4,34 mg QE/g ext and 83,28 ± 1,99 % respectively). The formulation liang tea and citrus peel with mass ration 60:40 showed the highest pH value (6,89 ± 0,04. The colour of tea formulation of liang tea and citur peel with mass ratio 70:30 showed colour characteristics are *L value (32,07 ± 0,06), *a (2,03 ± 0,06), *b (0,6 ± 0),*C (2,53 ± 0,06) and *h (15,23 ± 1,04).